Role of pharmacogenomics for prevention of hypersensitivity reactions induced by aromatic antiseizure medications - Alvarado, Angel T.; Zavaleta, Amparo Iris; Li-Amenero, César; Bendezú, María R.; Garcia, Jorge A.; Chávez, Haydee; Palomino-Jhong, Juan J.; Surco-Laos, Felipe; Laos-Anchante, Doris; Melgar-Merino, Elizabeth J.; Cuba-Garcia, Pompeyo A.; Yarasca-Carlos, Paulina E. (Frontiers in Pharmacology, 2025)
Epilepsy is the second most common neurological condition worldwide, characterized by recurrent, unprovoked, self-limiting seizures of genetic, acquired, or unknown origin. The objective was to describe the pharmacogenomic markers associated with hypersensitivity reactions induced by aromatic antiseizure medications. This review explored the pharmacokinetics, pharmacogenomics of CYP2C9 and HLA associated with hypersensitivity reactions, immunopathogenesis and its clinical implications. The included studies applied odds ratio (OR), 95% confidence interval (95% CI) and p value, as association statistics between severe cutaneous adverse reactions (SCARs) including Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). An association study was found between CYP2C19*2 and SCARs induced by carbamazepine, phenytoin and phenobarbital. Five studies of CYP2C9*3 associated with phenytoin-induced SCARs, four studies of CYP2C9*3, HLA-B*13:01, HLA-B*15:02, HLA-B*51:01 and HLA-B*55:01 HLA-B*46:01 and HLA-B*56:02/04 associated with phenytoin-induced SCARs. Likewise, six studies found an association between HLA-B*15:02 and carbamazepine-induced SJS/TEN, four studies associated HLA-A*02:07, HLA-A*24:02, HLA-A*33:03, HLA-B*15:02, HLA-B*44:03 with lamotrigine-induced SCARs, one study associated HLA-A*02:01, HLA-B*35:01, HLA-C*04:01, and HLA-C*08:01 with lamotrigine- and phenytoin-induced SCARs. Three association studies between HLA-A*02:01, HLA-A*11:01, HLA-A*24:02, HLA-B*15:02, HLA-B*38:01, HLA-B*40:02 and HLA-DRB1*03:01 with SCARs induced by carbamazepine, lamotrigine and phenytoin. Published scientific evidence demonstrates that CYP2C9*3 and various HLA alleles are associated with severe cutaneous adverse reactions such as toxic epidermal necrolysis and Stevens-Johnson syndrome. Neurologists should consider these allelic variants as predictive and preventive genetic biomarkers of severe adverse reactions to carbamazepine, phenytoin, phenobarbital, and lamotrigine, especially in Asian populations.